2012
DOI: 10.1177/0022034512444446
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Orthodontic Pain Control

Abstract: The objective of this study was to evaluate the efficacy of cognitive behavioral therapy intervention for patients who experienced pain during orthodontic treatment. The baseline characteristics were assessed via questionnaires and oral examinations. Four hundred and fifty eligible individuals were recruited and randomized by computer-generated block randomization into three groups: cognitive behavioral therapy intervention (n = 150), ibuprofen intervention (n = 150), and no intervention (control; n = 150). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 28 publications
4
37
1
Order By: Relevance
“…One of those studies assessed the effect of CBT on orthodontic patients also using a VAS, and it reported the significant lower pain with intervention of CBT [23]. However, we did not find significant differences in the standardized VAS score or raw VAS score.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…One of those studies assessed the effect of CBT on orthodontic patients also using a VAS, and it reported the significant lower pain with intervention of CBT [23]. However, we did not find significant differences in the standardized VAS score or raw VAS score.…”
Section: Discussioncontrasting
confidence: 67%
“…CBT was carried out according to a standard method [23] used in clinical psychology [20,21,24,25]. Briefly, the operator introduced herself, explained the experiment carefully, and then established rapport and trust with the subject.…”
Section: Cbtmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the therapists detailed the pain that might occur, and patients were assured that the pain would decrease gradually. 61 In the miscellaneous intervention class, the benzocaine local anaesthetic patch and transcutaneous electrical nerve stimulation were more effective (shared median rank of 20) than vibrational appliances. The lower effectiveness of vibration appliances could be because vibrations could have negated the pain-relieving ability of these appliances by actually hurting the already painful tooth from the orthodontic forces.…”
Section: Discussionmentioning
confidence: 99%
“…This pain may persist for the following 3-5 days (Bradley et al 2007). The most common intervention for the management of such pain is the use of oral analgesics, for example ibuprofen or paracetamol (Xiaoting et al 2010), although other methods have been suggested including electrical stimulation (TENS machines) (Roth & Thrash 1986;Weiss & Carver 1994), plastic chews (Hwang et al 1994;Otasevic et al 2006), tooth vibration (Marie et al 2003), cognitive behavioural therapy (Wang et al 2012) and text message follow up (Keith et al 2013). Interestingly a study on the use of a follow up telephone call reported that the level of perceived orthodontic pain was reduced following the call, but was unaffected by its content, i.e.…”
Section: Introductionmentioning
confidence: 99%